A contribution of optimism and social support to adversity quotient - Desy Putri Rahmadina; Ririanti Rachmayanie Jamain; Novitawati Novitawati (Universitas Negeri Padang, 2023)
The difficulties experienced by students often make them want to give up or even run away from a problem. If someone wants to achieve success, he must have high fighting power in order to get maximum results. The ability of students to survive in difficult times is needed to be able to overcome these challenges.The purpose of this study was to analyze the contribution of optimism and social support to the adversity quotient of SMA Negeri 2 Banjarmasin students. This study uses a quantitative approach to the type of correlational research. The data collection tool used a social support and adversity question scale questionnaire, a sample of 306 was obtained from 1,039 students of SMA Negeri 2 Banjarmasin using the proportionate stratified random sampling technique. Data analysis techniques using descriptive statistics and multiple linear regression. The results of the study stated that the contribution of optimism and social support to the adversity quotient was 70.9%, meaning that students had an optimistic attitude due to social support so they were able to show their adversity questient. If students are able to face and the environment provides encouragement or assistance then they have an optimistic attitude and high social support.